American pastoral. - Roth, Philip, ....- (London : Vintage, 1998)
Seymour 'Swede' Levov - a legendary high school athlete, a devoted family man, a hard worker, the prosperous inheritor of his father's Newark glove factory - comes of age in thriving, triumphant post-war America. But everything he loves is lost when the country begins to run amok in the turbulent 1960s. American Pastoral is the story of a fortunate American's rise and fall - of a strong, confident master of social equilibrium overwhelmed by the forces of social disorder.
Keywords: Fiction